Photo-Fenton Treatment Of Sago Wastewater: Rsm Optimization And Toxicity Evaluation - Kanakaraju, Devagi; Wong, Soon Pang; Wan Abu Bakar, Wan Azelee (UTM, 2018)
Due to the fact that organic matter in sago wastewater is not effectively removed by current traditional methods, this study was designed to systematically investigate the performance of photo-Fenton treatment. Despite being ratified for its high efficiency in improving wastewater quality, there remains a paucity of evidence on its performance on sago wastewater. Thus, the objective of this study was to optimize the conditions of the photo-Fenton process by employing the response surface methodology (RSM) using the chemical oxygen demand (COD) removal as the target parameter. Fenton’s reagent (Fe2+ and H2O2 concentration) and pH were used as the independent variables to be optimized. Under optimum conditions, 90.0% of COD removal efficiency was obtained when the wastewater sample was treated at pH 2.66 in the presence of 4.01 g/L of H2O2and 5.07 g/L Fe2+ion. Despite the high COD removal, the total organic carbon (TOC) removal under the same optimized condition was lower, only 48.0% indicating incomplete mineralization of stable intermediates present in the solution. Toxicity evaluation revealed that the mortality of Artemia salina was less than 50%, which means that the treated sago wastewater can be considered as non-toxic. The regression value (R2> 0.99) of the models indicates a high degree of correlation between the parameters evaluated. The results obtained indicate the feasibility of photo-Fenton treatment to the sago wastewater as an appealing alternative approach.